Optimal fosamprenavir regimen to prevent lipid abnormalities - Lattuada, E.; Lanzafame, M.; Grosso, C.; Soldani, et al., F. (Acta Biomedica Atenei Parmensis, 2009)
We report our experience on the impact of different fosamprenavir boosted regimens on plasma lipid levels in 48 naïve monoinfectd- HIV-seropositive patients. Eighteen months after starting antiretroviral therapy (ART), all patients showed a good immuno-virological response, with no statistically significant differences among the three groups; no changes in ART regimens were necessary and no adverse events were reported. On the contrary, a statistically significant difference among the three groups of patients was observed in cholesterol and triglyceride levels, since higher levels of cholesterol (including LDLs) and triglycerides were observed in patients taking the higher dose of ritonavir.